ANALISIS KEBUTUHAN AIR BERSIH PDAM KOTA PADANG PANJANG - Kurniawan, Jefri; Masril, Masril; Hafnil, Jon (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The need for clean water is a crucial aspect in ensuring a decent quality of life for the residents of a city. In this context, the Regional Drinking Water Company (PDAM) plays a vital role in providing an adequate water supply. This research aims to analyze the demand for clean water and the availability of the water supply from PDAM Kota Padang Panjang until 2027. The methods employed include the analysis of population projection, direct connections, clean water demand, required water flow, water loss, and water balance. Primary and secondary data were obtained from PDAM Kota Padang Panjang. The analysis results indicate that the demand for PDAM clean water reaches 6,433,781.2 m³/year or 204 l/s, while the water supply availability is only 3,362,947.2 m³/year or 106.7 l/s. With a deficit of 97.3 l/s, the demand for clean water by the community remains unmet until 2027. This study contributes to a better understanding and management of water resources to support the needs of the residents of Kota Padang Panjang.Keywords : Water, Discharge, Infrastructure, water resources